The Negotiation of Political Identity and Rise of Social Citizenship: A Study of the Former Female Combatants in Aceh Since the Helsinki Peace Accord - Arifah Rahmawati; Dewi H Susilastuti; Mohtar Mas'oed; Muhadjir Darwin (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
An identity negotiation process, initiated after the peace agreement was reached, is currently underway in Aceh. This can be seen, for example, in the activities of the women joined in the Inong Balee troop, the women's wing of the Free Aceh Movement (Gerakan Aceh Merdeka, GAM) formed in the late 1990s. Their participation as women combatants is inseparable from the strong ethno-nationalistic identity and ethno-political struggle that sought Aceh's independence. Today, more than twelve years after peace was reached in Aceh, the Acehnese ethno-political identity has experienced a transformation. Although it has not entirely disappeared, their activities have been framed as part of Indonesian nationalism. This finding emphasizes that nation is not fixed, but transformable and negotiable. The once ethno-political identity has become a social national identity. This paper attempts to understand how former woman members of GAM through a qualitative narrative. This paper attempts to answer why this has happened and how former combatants have negotiated their identities. Is there still a sense of Acehnese nationalism, as they fought for, and how has this intersected with their Indonesian nationalism since they became ordinary citizens?